Excitotoxicity as a Target Against Neurodegenerative Processes - Binvignat, Octavio; Olloquequi, Jordi (Current Pharmaceutical Design, 2020)
The global burden of neurodegenerative diseases is alarmingly increasing in parallel to the aging of population. Although the molecular mechanisms leading to neurodegeneration are not completely understood, excitotoxicity, defined as the injury and death of neurons due to excessive or prolonged exposure to excitatory amino acids, has been shown to play a pivotal role. The increased release and/or decreased uptake of glutamate results in dysregulation of neuronal calcium homeostasis, leading to oxidative stress, mitochondrial dysfunctions, disturbances in protein turn-over and neuroinflammation. Despite the anti-excitotoxic drug memantine has shown modest beneficial effects in some patients with dementia, to date, there is no effective treatment capable of halting or curing neurodegenerative diseases such as Alzheimer’s disease, Parkinson disease, Huntington’s disease or amyotrophic lateral sclerosis. This has led to a growing body of research focusing on understanding the mechanisms associated with the excitotoxic insult and on uncovering potential therapeutic strategies targeting these mechanisms. In the present review, we examine the molecular mechanisms related to excitotoxic cell death. Moreover, we provide a comprehensive and updated state of the art of preclinical and clinical investigations targeting excitotoxic- related mechanisms in order to provide an effective treatment against neurodegeneration.
Keywords: oxidative stress